The Uptake Mechanism of Cd(II), Cr(VI), Cu(II), Pb(II), and Zn(II) by Mycelia and Fruiting Bodies of Galerina vittiformis - Dilna Damodaran (BioMed Research International, 2013)
Optimum concentrations of heavy metals like copper, cadmium, lead, chromium, and zinc in soil are essential in carrying out various cellular activities in minimum concentrations and hence help in sustaining all life forms, although higher concentration of these metals is lethal to most of the life forms. Galerina vittiformis, a macrofungus, was found to accumulate these heavy metals into its fleshy fruiting body in the order Pb(II) > Cd(II) > Cu(II) > Zn(II) > Cr(VI) from 50 mg/kg soil. It possesses various ranges of potential cellular mechanisms that may be involved in detoxification of heavy metals and thus increases its tolerance to heavy metal stress, mainly by producing organic acids and phytochelatins (PCs). These components help in repairing stress damaged proteins and compartmentalisation of metals to vacuoles. The stress tolerance mechanism can be deduced by various analytical tools like SEM-EDX, FTIR, and LC-MS. Production of two kinds of phytochelatins was observed in the organism in response to metal stress.